Цифрові трансформації як сучасний тренд періодичного циклу розвитку суспільства - Квітка, Сергій (My University, 2020)
Актуальність теми пов’язана з активізацією цифрової трансформації суспільства в зв'язку з початком світової економічної кризи. Метою даної роботи є обґрунтування того, що цей процес є не черговим етапом у розвитку інформаційного суспільства, а є новим етапом у розвитку людства.

The urgency of the topic is related to the intensification of the digital transformation of society in connection with the beginning of the global economic crisis. The purpose of this work is to substantiate that this process is not another stage in the development of the information society, but is a new stage in the development of mankind.
Digital transformations as a modern trend of the periodic cycle of society development
Keywords: цифрова трансформація; «довгі хвилі»; структурна криза; digital transformation; «long waves»; structural crisis